Oral History Program Interview: Vivian Leah Barnes Kirschenmann - Kirschenmann, Vivian Leah Barnes
Kirschenmann was born in Boynton, Muskogee County, Oklahoma on March 1, 1920. She and her family came to Shafter, California in 1929. Kirschenmann's account on discrimination towards "Okies" and African Americans, race relations, the Ku Klux Klan and Sundown Towns, dugout and "state" homes, rabbit drives, and the types of food cooked is a fascinating woman's perspective of life prior to and during the Dust Bowl.